63. Multicenter protocol on the role of ultrasound in immune-mediated neuropathies. Issue 1 (January 2015) - Paolasso, I.; Hobson-Webb, L.; Briani, C.; Tsukamoto, H.; Coraci, D.; Erra, C.; Granata, G.; Padua, L.
<x xml:space="preserve">Abstract</x> Immune-mediated neuropathies include clinically heterogeneous disorders such as Guillain–Barré syndrome (GBS) and its variants, chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), multifocal motor neuropathy (MMN), neuropathy with monoclonal gammopathy and others. High-resolution ultrasound (US) is a helpful technique for the evaluation of peripheral nerves. In previous studies on immune-mediated neuropathies, nerve US showed diffuse enlargement of cross sectional area (CSA) of peripheral nerves trunks and cervical roots and morphological alterations at conduction block site. Data are however heterogeneous, correlations with clinical history or disease severity are lacking and there are no longitudinal studies in literature. The objective of the protocol is to prospectively evaluate, through a multicenter longitudinal study, nerve US findings in patients with newly diagnosed immune-mediated neuropathies and evaluate the relationship with clinical and neurophysiological findings and changes over time (natural history) or in response to therapy. The protocol includes clinical assessment, neurophysiological examination, US examination of median, ulnar, radial, fibular, tibial, sural nerves (and brachial plexus in extended protocol) with evaluation of maximal/minimal CSA for each nerve, inter- and intra-nerve variability, US classification depending on echogenicity and fascicles enlargement. US and neurophysiological follow-up timing examinations follow different schedules in acute and chronic immune-mediated disease. We present preliminary results and feasibility of the protocol.